Microsoft Word step by step - Lambert, Joan (Step by step (Redmond, Wash.), 2022)
The quick way to learn Microsoft Word 365 and Word 2021 for Windows! This is learning made easy. Get more done quickly with Microsoft Word. Jump in wherever you need answers brisk lessons and detailed screenshots show you exactly what to do, step by step. Create great-looking, well-organized, accessible documents to enhance communication Use headings, bookmarks, and footnotes for more intuitive access to knowledge Present complex information in diagrams and charts Illustrate concepts by using professional stock images, 3D models, icons, and screen clippings Collaborate with other Word and Word for the web users to create and edit documents in real time, tracking changes for review and automatically saving file versions Enforce security and privacy in electronic documents Quickly build tables of contents, indexes, and bibliographies Generate personalized emails, letters, labels, envelopes, directories, and catalogs from various data sources Supercharge efficiency with custom styles, themes, templates, and building blocks Look up just the tasks and lessons you need.